Nature, Land, and Sustainability: Exploring the Livelihood Strategies of Local Community and Development of “Billionaire Village” in Tuban Regency, Indonesia - Rahmawati, Deti; Susilowati, Endang (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
Rural communities depend on natural resources for their livelihoods. As such, managing nature, land, and the environment is crucial. This study examines the livelihood assets and lives of the community following land compensation from a company establishing its presence in the region. This study employs purposive sampling, a method commonly used in quantitative research, to represent communities affected by industrial activity in Wadung Village, Jenu District, Tuban Regency, Indonesia. The participants consist of 30 fishermen and farmers. They filled out the survey for the primary data in this study. The findings show that land loss has significantly transformed the environmental ecosystem and the sustainability of life. This study examines five sustainable livelihood capitals—natural, social, financial, physical, and human capital. Social capital scored highest (14.78), reflecting the community's strong interpersonal networks and active community organizations. Financial capital ranked second (14.70), largely due to substantial compensation payments following land acquisition. However, these funds have led to financial management challenges, as many recipients lack financial literacy and spend compensation money on consumer goods rather than long-term investments. This spending pattern, combined with significant livelihood disruptions (including career changes and relocations after land loss), has created a need for structured financial guidance to ensure sustainable use of compensation funds.